Abandono do tratamento clínico fonoaudiológico: estudo exploratório em Fortaleza-Ceará - Soares, Maria do Socorro Távora (2001)
This study investigates the abandonment of the speech therapy clinical treatment in a reference hospital from Fortaleza-Ceara. A qualitative approach of sense production was adopted to quotidian, based in the social constructcionism, searching for understand the interviewers's meanings on health-disease process in the vocal disturbance, speech therapy clinical treatment, associated factors about treatment adandon, access to health services and strategies to improve it. Seventeen semj-structured interviews were accomplished and the collective material were organized in ideas association maps, through the builted arguments and presentation of speeches spaces, with the significance diagrams formation that reflects the research objectives and the senses that comes from investigated field, trying to give visibiity to the interpretation process. The vocal disturbance should be seen in a generic way, having in mind, besides the vocal manifestation, the physical dynamics, intellectual, emotional, cultural and social of each person. In the investigated field the abandonment of the speech therapy clinical treatment happened for several difficulties as: to conciliate work and treatment; the way to transport to health unit; social and economics reasons; appearance or worsening of psychological disturbs; crisis or emergence of associated general diseases; personal factors; the growing better in the clinical picture with the suppression of symptoms; access difficulties to the public health services, besides others problems in the doctor-patient relationship. A series of biological, psychological, social, economics and personal factors are observed and associated to the treatment abandon.